2000
DOI: 10.1152/jappl.2000.88.4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Creatine reduces human muscle PCr and pH decrements and Piaccumulation during low-intensity exercise

Abstract: The purpose of this study was to examine with (31)P-magnetic resonance spectroscopy energy metabolism during repeated plantar flexion isometric exercise (Ex-1-Ex-4) at 32 +/- 1 and 79 +/- 4% of maximal voluntary contraction (MVC) before and during a creatine (Cr) feeding period of 5 g/day for 11 days. Eight trained male subjects participated in the study. ATP was unchanged with Cr supplementation at rest and during exercise at both intensities. Resting muscle phosphocreatine (PCr) increased (P < 0.05) from 18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 45 publications
4
35
1
Order By: Relevance
“…Cr supplementation, which aims to increase PCr stocks, leads to higher ATP resynthesis capacity (GREENHAFF, 1997;TERJUNG et al, 2000;RICO-SANZ, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cr supplementation, which aims to increase PCr stocks, leads to higher ATP resynthesis capacity (GREENHAFF, 1997;TERJUNG et al, 2000;RICO-SANZ, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of Cr in the increase in corporal mass, performance in exercises of high intensity and exercises of short duration has been confirmed, showing it to be one of the most popular supplements in the world (BRANCH, 2003) It is believed that Cr can help the maintenance of high energy phosphate during exercise, increasing performance in several activities such as high intensity exercises, repeated tasks of intensity with frequent pauses, more prolonged anaerobic tasks, and sports activities of endurance, increasing creatine phosphate (PCr) stocks, and leading to a higher ATP resynthesis capacity (ARAÚJO et al, 2013;PERSKY;BRAZEAU, 2001;RICO-SANZ, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports showed that creatine supplementation enhances oxidative phosphorylation and creatine has direct scavenger effects. [6][7][8] Guidi et al 24 reported that creatine has a protective effect on oxidatively injured mtDNA. Sestili et al 8 also reported cytoprotective effect of creatine on oxidatively injured cultured mammalian cells through direct antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine has been reported to have antiinflammatory, antioxidant effects and it has been shown that it acts as a free radical scavenger. [4][5][6][7][8] Besides this, recent reports supported that Cr has additional beneficial effects on various neurological, muscular, cardiovascular disorders, and aging. [9][10][11][12][13][14] The aim of this study is to investigate the possible protective effect of creatine therapy on cisplatin-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 88%